(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
In these days, a number of students are learning second language as well as this way has a lot of difficulties. The findings of the study indicate that students prefer to engage in the vocabulary learning strategies that would be most appealing to them and that would entail less manipulation of the language. Of the four vocabulary memorizing strategies cited in the study rote repetition, structural associations, semantic strategies, and mnemonic keyword techniques, students apparently tended to favor the second and the third ones, though rote repetition remains appealing to some of them.